1980
DOI: 10.1177/004912418000900205
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Measurement Error in Status Attainment Models

Abstract: This article investigates sex differences in the accuracy of young adults' retrospective reports of parental status using Joreskog's general framework for the simultaneous covariance structure analysis of multiple populations. Results indicate that young women's reports of maternal education are significantly more reliable than are young men's reports and that the reliabilities of reports ofpaternal traits are similar for young men and women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

1986
1986
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 15 publications
1
10
1
Order By: Relevance
“…Reliability, defined in this way, has been used in a number of applications aimed at understanding the extent of randomness in survey response (e.g. see Achen, 1975;Alwin, 1989aAlwin, , 1989bKrosnick, 1989a, 1989b;Alwin and Thornton, 1984;Andrews, 1984;Asher, 1974;Bieiby and Hauser, 1977;Featherman, 1977a, 1977b;Borus and Nestle, 1973;Converse and Markus, 1979;Corcoran, 1980;Erikson, 1979;Hauser, Tsai and Sewell, 1983;Jagodzinski and Kuhnei, 1987;Marquis and Marquis, 1977;Siegel and Hodge, 1968;Smith and Stephenson, 1979). The general conclusion of this body of work is that unreliability of measurement occurs with respect to a wide variety of content areas, and while the measurement of attitudes may be particularly difficult (Converse, 1964), substantial amounts of error occur in the measurement of other phenomena as well.…”
Section: The Concept Of Reliabilitymentioning
confidence: 99%
“…Reliability, defined in this way, has been used in a number of applications aimed at understanding the extent of randomness in survey response (e.g. see Achen, 1975;Alwin, 1989aAlwin, , 1989bKrosnick, 1989a, 1989b;Alwin and Thornton, 1984;Andrews, 1984;Asher, 1974;Bieiby and Hauser, 1977;Featherman, 1977a, 1977b;Borus and Nestle, 1973;Converse and Markus, 1979;Corcoran, 1980;Erikson, 1979;Hauser, Tsai and Sewell, 1983;Jagodzinski and Kuhnei, 1987;Marquis and Marquis, 1977;Siegel and Hodge, 1968;Smith and Stephenson, 1979). The general conclusion of this body of work is that unreliability of measurement occurs with respect to a wide variety of content areas, and while the measurement of attitudes may be particularly difficult (Converse, 1964), substantial amounts of error occur in the measurement of other phenomena as well.…”
Section: The Concept Of Reliabilitymentioning
confidence: 99%
“…Further, note should be taken of the work which has shown that sub-groups in the population may exhibit varying patterns of response error (Mason et al, 1976;Bielby et al, 1977: Corcoran, 1980Wyner, 1981;Mare and Mason, 1980;Hamilton, 1981) and, of the research on the stability of underlying true scores across time (Wheaton et al, 1977). We would like some information on the Highers you have taken, N.B.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of social background on son's educational attainment and the effect of father's occupational status on son's occupational status are stronger when fathers' information was used. Corcoran (1980Corcoran ( , 1981 used data from interviews with both young adults and their parents. The offspring turned out to make answers on different parental characteristics more consistent than they really were.…”
Section: Previous Researchmentioning
confidence: 99%
“…The studies of Broom et al (1978), Corcoran (1980Corcoran ( , 1981, Hauser et al (1983), Massagli and Hauser (1983), and Van Eijck (1996) discussed above use this design. This is the design we prefer, since the multiple source type design is not feasible for most family background variables, and because the multiple moment design respondents can give the same wrong answers in each interview.…”
Section: Multiple Informant Designmentioning
confidence: 99%